Peran Orang Tua dalam Mendukung Literasi Dini Anak pada Era Digital - Annisa Nur; Nur Hikmah; Marlina Marlina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Early literacy serves as an essential foundation that plays a crucial role in shaping the cognitive, social, and emotional development of young children. It extends beyond the ability to read and write, encompassing skills such as listening, speaking, and comprehensively understanding information in a holistic manner. In the digital era, these skills have become increasingly critical as children are exposed to diverse forms of information through technology, including digital books, educational applications, and interactive learning videos. Technology presents significant opportunities to support early literacy development in innovative and engaging ways. However, the digital age also poses notable challenges, such as the risk of distraction from entertainment content, exposure to age-inappropriate information, and disparities in access to technology across different social groups. This study aims to deeply explore the strategic role of parents in supporting early literacy development in the digital era, including the strategies they employ, the challenges they face, and the impacts of their involvement. Using a qualitative-descriptive approach, the research analyzes data from in-depth interviews, observations of parent-child interactions, and recent literature on early literacy and technology. The findings indicate that active parental involvement, both through technology-based approaches and traditional methods, significantly enhances children's literacy skills. Nonetheless, the study also identifies various challenges commonly encountered, such as time constraints, low digital literacy among parents, and inequities in technology access. This article underscores the importance of synergy between technological and conventional approaches to create a holistic and sustainable literacy environment. It provides in-depth insights into the critical role of parental support in the digital era and offers practical recommendations to address existing barriers, ensuring that early literacy development proceeds optimally and aligns with contemporary needs.